The Image of Death in the Texts of the Ket Linguoculture (Proceedings of Southern Federal University. Philology, 2021)
Oleg A. Alexandrov (Tomsk, Russian Federation)A fragment of the linguistic view of the world of the Kets, a minority ethnos, whose language is going through a period of shift, is reconstructed. The category of mortality is implicated on the basis of vocabulary united by the meanings “death”, “to die”. Through the analysis of contexts, including this vocabulary, the peculiarities of the linguistic representation of ideas about the category of death are revealed and cognitive-figurative models that order these representations are identified.As a result of the study, it is found that metaphorization and description of visual signs in the Ket language act as key mechanisms for the linguization of the phenomenon of death, and the meanings expressed in discourse reveal an ambivalent and antinomic character. Along with such metaphors as “eternal sleep,” “withdrawal into another world,” the Ket discourse of death also contains direct descriptions of objective ones, i.e. visible manifestations of the category under discussion - cessation of breathing, inability to move, etc. An analysis of the Ket discourse of death indicates that the belief in the immortality of the soul and the other world, expressed in it, is intended to neutralize the fear of death. On the other hand, plots are revealed that express the possibility of struggle and victory over death. This indicates that death is understood as an undesirable, frightening phenomenon that opposes the successful course of a person’s life events.Key words: Ket language, linguistic view of the world, image of death, discourse, metaphor.DOI 10.18522/1995-0640-2021-2-29-38